Introduction: Batavian Phlegm? The Dutch and their Emotions in Pre-Modern Times - Roodenburg, Herman; Santing, Catrien (BMGN - Low Countries Historical Review, 2014)
In the autumn of 2011 the Royal Dutch Historical Society held its annual autumn conference. The theme was Cool, Calm and Collected: The Dutch and their Emotions in Pre-Modern Times. This introduction to the subsequent special issue of the BMGN -Low Countries Historical Review gives a brief historiographical overview of the history of emotions in general and its scant practice to date in the Northern Netherlands. Seven case-studies are introduced that show that the assumed phlegmatic character of the Dutch was a relatively late construction, coming into being in the course of the eighteenth century. Earlier descriptions of local and regional characteristics vary widely. Although most of the earlier authors mention the negative influence of the damp living conditions on the Dutch, just as frequently passionate behaviour, expressing vivacity, anger and heightened sentiments, was deemed typical of the freedom-loving barbarians from the north. The current national hero Desiderius Erasmus for example was known for his jealous, rash and overly emotional temper. This introduction is part of the special issue 'Batavian Phlegm?'. Bataafs Flegma? De Nederlanders en hun emoties in de Premoderne TijdHet najaarscongres van het KNHG had in 2011 als thema Cool, Calm and Collected: The Dutch and their Emotions in Pre-Modern Times. Deze introductie op het daaruit voortvloeiende themanummer van BMGN - Low Countries Historical Review geeft zowel een kort historiografisch overzicht van de emotiegeschiedenis in het algemeen als van haar (bescheiden) beoefening tot nu toe in Nederland. Zeven casussen laten zien dat de veronderstelde flegmatische volksaard van de Nederlander een late constructie was die in loop van de achttiende eeuw tot stand kwam. Vroegere beschrijvingen van lokale of regionale kenmerken lopen nogal uiteen. Hoewel de meeste oudere auteurs de negatieve invloed van de vochtige leefomstandigheden op de Nederlanders wel onderkenden, beschouwden zij evenzeer onbesuisd gedrag dat vrolijkheid, boosheid en verhitte gevoelens uitdrukte, als typerend voor de vrijheidslievende barbaren uit het noorden. Desiderius Erasmus bijvoorbeeld, tegenwoordig onderdeel van de Canon van de Nederlandse geschiedenis, stond bekend om zijn jaloerse, onstuimige en emotionele karakter.Deze introductie maakt deel uit van het themanummer 'Batavian Phlegm?'.